THE EFFECT OF CAPITAL, BUSINESS DURATION, AND TECHNOLOGY UTILIZATION ON THE INCOME OF MSME ACTORS IN THE TRADE SECTOR IN SOUTH DENPASAR - Novia Ramadhani Savitri; Made Kembar Sri Budhi (Adisam Publisher, 2025)
Micro, Small, and Medium Enterprises (MSMEs) constitute a major component of the economy, playing a vital role in supporting national economic development and significantly contributing to local economies. The trade sector, as one of the prominent MSME sectors, has experienced substantial growth and remains highly attractive to the public in South Denpasar District. This strong growth potential inevitably intensifies competition among MSME actors, necessitating greater creativity and innovation. This study aims to examine the effect of capital, business duration, and technology utilization on the income of MSME actors in the trade sector in South Denpasar, both simultaneously and partially. The study was conducted in South Denpasar District, with a population of 3,306 trade-sector MSME units and a sample of 97 respondents selected using purposive sampling. The types of data used include both qualitative and quantitative data. The analytical techniques applied are descriptive analysis and multiple linear regression analysis. The results indicate that all independent variables have a significant simultaneous effect on the dependent variable. Partially, capital, business duration, and technology utilization each have a positive and significant effect on the income of MSME actors in the trade sector in South Denpasar.